MANAGEMENT OF DELIRIUM IN THE ELDERLY - dos Santos, Lucas Xavier; Diniz, Yngryson Almeida; Melo, Maria Larissa do Nascimento; Marcheti, Renan Schmitz; Kois, Nailon de Morais; da Silva, Maria Clara Teixeira; de Castilho, Pedro Augusto Godinho; Dantas, Miquéia Aurélia Vieira Diniz; da Silva, Mike Draiher; Bazana, Gustavo Stanislaski; Pereira, Hercia Simone Palhano Oliveira; Santos, Rubia Martinez (Seven Editora, 2026)
Postoperative delirium (POD) is one of the most frequent and serious complications in elderly patients undergoing surgical procedures, characterized by acute and fluctuating disturbances of attention, consciousness, and cognition. Its occurrence is associated with significant adverse outcomes, including increased morbidity and mortality, prolonged hospital stay, functional and cognitive decline, institutionalization, and increased healthcare costs. The pathophysiology of POD is complex and multifactorial, involving the interaction between underlying brain vulnerability (predisposing factors) and acute perioperative stressors (precipitating factors). Predisposing factors include advanced age, frailty, malnutrition, multimorbidity, previous cognitive impairment, and depression. Precipitating factors include major surgeries, systemic inflammatory response, intraoperative hypotension, poorly controlled pain, and the use of medications such as benzodiazepines. Prevention of postoperative delirium (POD) is based on multicomponent non-pharmacological interventions, such as those proposed by the Hospital Elder Life Program (HELP), which have demonstrated effectiveness in reducing the incidence of the condition. Comprehensive Geriatric Assessment (CGA) in the preoperative period allows for the systematic optimization of modifiable risk factors. Evidence for pharmacological prophylaxis is limited, with dexmedetomidine standing out as a promising option in selected populations, while benzodiazepines should be avoided. Machine learning-based prediction models have demonstrated superior accuracy to traditional logistic regression in identifying high-risk patients, incorporating biomarkers such as brain natriuretic peptide (BNP), troponin T, and C-reactive protein. The relationship between delirium and dementia is intimate and bidirectional, with delirium frequently underdiagnosed in patients with pre-existing dementia. The clinical approach should prioritize the identification and management of triggering factors in all confused elderly individuals, regardless of suspicion of underlying dementia.